ASPP2 enhances Oxaliplatin (L‐OHP)‐induced colorectal cancer cell apoptosis in a p53‐independent manner by inhibiting cell autophagy. Issue 3 (23rd December 2014) - Shi, Ying; Han, Yue; Xie, Fang; Wang, Anna; Feng, Xiaokun; Li, Ning; Guo, Hongliang; Chen, Dexi
Abstract Inactivation of p53‐mediated cell death pathways is a central component of cancer progression. ASPP2 (apoptosis stimulated protein of p53‐2) is a p53 binding protein that specially stimulates pro‐apoptosis function of p53. Down‐regulation of ASPP2 is observed in many human cancers and is associated with poor prognosis and metastasis. In this study, ASPP2 was found to enhance L‐OHP‐induced apoptosis in HCT116 p53−/− cells in a p53‐independent manner. Such apoptosis‐promoting effect of ASPP2 was achieved by inhibiting autophagy. Further experiments with ASPP2 RNA interference and autophagy inhibitor (3‐methyladenine, 3‐MA) confirmed that ASPP2 enhanced HCT116 p53−/− cell apoptosis via inhibiting the autophagy. The association of cell death and autophagy was also found in ASPP2+/− mice, where colon tissue with reduced ASPP2 expression displayed more autophagy and less cell death. Finally, colorectal tumours and their adjacent normal tissues from 20 colorectal cancer patients were used to examine ASPP2 expression, p53 expression and p53 mutation, to understand their relationships with the patients' outcome. Three site mutations were found in p53 transcripts from 16 of 20 patients. ASPP2 mRNA expressions were higher, and autophagy level was lower in the adjacent normal tissues, compared with the tumour tissues, which was independent of both p53 mutation and expression level. Taken together, ASPP2 increased tumour sensitivity to chemotherapy via inhibiting autophagy in a p53‐independent manner, which was associated with the tumour formation, suggesting that both p53 inactivation and ASPP2 expression level were involved in the sensitivity of colorectal cancer to chemotherapy.